How to Efficiently Reconfigure Tunable Lookup Tables for Dynamic Circuit Specialization. (21st March 2016) - Kulkarni, Amit; Stroobandt, Dirk
Abstract : Dynamic Circuit Specialization is used to optimize the implementation of a parameterized application on an FPGA. Instead of implementing the parameters as regular inputs, in the DCS approach these inputs are implemented as constants. When the parameter values change, the design is reoptimized for the new constant values by reconfiguring the FPGA. This allows faster and more resource-efficient implementation but investigations have shown that reconfiguration time is the major limitation for DCS implementation on Xilinx FPGAs. The limitation arises from the use of inefficient reconfiguration methods in conventional DCS implementation. To address this issue, we propose different approaches to reduce the reconfiguration time drastically and improve the reconfiguration speed. In this context, this paper presents the use of custom reconfiguration controllers and custom reconfiguration software drivers, along with placement constraints to shorten the reconfiguration time. Our results show an improvement in the reconfiguration speed by at least a factor 14 by using Xilinx reconfiguration controller along with placement constraints. However, the improvement can go up to a factor 40 with the combination of a custom reconfiguration controller, custom software drivers, and placement constraints. We also observe depreciation in the system's performance by at least 6% due to placement constraints.